2019
DOI: 10.1177/0047287519835969
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Facebook Statistics in Tourism Demand Modeling and Destination Marketing

Abstract: Facebook is a popular social media platform used by both the demand and the supply sides of the tourism industry. Since there is a huge amount of information on the Internet, which can lead to information overload, individuals tend to apply the principle of least effort in attempting to obtain useful information as quickly and easily as possible. One of the easiest ways to retrieve travel information is by visiting the Facebook pages of destinations. This study investigates the foundations of the usefulness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 55 publications
2
40
0
2
Order By: Relevance
“…Numerous studies in tourism and hospitality fields have profiled tourists' UGC sharing/using behaviors on social media platforms (e.g., Bigné, William, and Soria-Olivas 2020;Bronner and de Hoog 2011), identified content types likely to be shared or found useful on social media (e.g., Önder, Gunter, and Gindl 2020), and revealed factors that influence UGC sharing (e.g., trip satisfaction/dissatisfaction and previous sharing experiences) and using behaviors (e.g., UGC usefulness, trust in and perceived preferential similarity to sharers) (e.g., Oliveira, Araujo, and Tam 2020;Shin, Perdue, and Pandelaere 2020). Research also identified effects on tourist expectations and purchase intentions from posted UGC characteristics (e.g., ratings, valence, lengths, readability, and language style) and from sharer characteristics (e.g., travel and posting frequencies) (e.g., Liu, Wu, and Li 2019;Kaosiri et al 2019).…”
Section: Ugc Studies In Tourism and Hospitalitymentioning
confidence: 99%
“…Numerous studies in tourism and hospitality fields have profiled tourists' UGC sharing/using behaviors on social media platforms (e.g., Bigné, William, and Soria-Olivas 2020;Bronner and de Hoog 2011), identified content types likely to be shared or found useful on social media (e.g., Önder, Gunter, and Gindl 2020), and revealed factors that influence UGC sharing (e.g., trip satisfaction/dissatisfaction and previous sharing experiences) and using behaviors (e.g., UGC usefulness, trust in and perceived preferential similarity to sharers) (e.g., Oliveira, Araujo, and Tam 2020;Shin, Perdue, and Pandelaere 2020). Research also identified effects on tourist expectations and purchase intentions from posted UGC characteristics (e.g., ratings, valence, lengths, readability, and language style) and from sharer characteristics (e.g., travel and posting frequencies) (e.g., Liu, Wu, and Li 2019;Kaosiri et al 2019).…”
Section: Ugc Studies In Tourism and Hospitalitymentioning
confidence: 99%
“… Assaker, Hallak, & El-Haddad, 2020 ; Ayer, 2015 ; Ayer, Au, & Law, 2013a ; Mendes-Filho, Mills, Tan, & Milne, 2018 ); UGC's impacts on travel organisations and destination marketing (e.g. Baka, 2016 ; Marine-Roig, 2017 ; Taecharungroj & Mathayomchan, 2019 ; Zhang, Zhang, & Yang, 2016 ; Önder, Gunter, & Gindl, 2020 ); and user intentions to engage into online travel communities (e.g. Ben-Shaul & Reichel, 2018 ; Bilro, Loureiro, & Guerreiro, 2019 ; Filieri, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These options range from a simple chat or email conversation to blogs and discussion groups (Miguens et al, 2008). Facebook is one of the most popular social media platforms and is utilized by both the demand and the tourism industry's supply sides (Önder et al, 2019 andAlghizzawi et al, 2019). Hanan and Petit (2014, 471) describe Instagram as one of the most frequently used image-based social media applications in the world and as "a trendy tool in digital tourism where snapshots and comments can be shared all across one's social media channels within seconds, and anybody could be in expressing their likes or dislikes towards a place of interest."…”
Section: Social Media and Tourist Destinationsmentioning
confidence: 99%